Associations of genetically determined iron status across the phenome: a mendelian randomization study - Gill,D; Benyamin,B; Moore,LSP; Monori,G; Zhou,A; Fotios,K; Evangelou,E; Laffan,M; Walker,AP; Tsilidis,KK; Dehghan,A; Elliott,P; et al. (PLoS Medicine, 2019)
BackgroundIron is integral to many physiological processes and variations in its levels, even within the normal range, can have implications for health. The objective of this study was to explore the broad clinical effects of varying iron status.Methods and FindingsGenome-wide association study summary data obtained from 48,972 European individuals (55% female) across 19 cohorts in the Genetics of Iron Status Consortium were used to identify three genetic variants (rs1800562 and rs1799945 in the hemochromatosis gene, and rs855791 in the transmembrane protease serine 6 gene) that associate with increased serum iron, ferritin and transferrin saturation, and decreased transferrin levels, thus serving as instruments for systemic iron status. Phenome-wide association study (PheWAS) of these instruments was performed on 415,482 European individuals (54% female) in the UK Biobank that were aged 40-69 years when recruited from 2006 to 2010, with their genetic data linked to Hospital Episode Statistics from April 1995 to March 2016. Two-sample summary data Mendelian randomization (MR) analysis was performed to investigate the effect of varying iron status on outcomes across the human phenome. MR-PheWAS analysis for the three iron status genetic instruments was performed separately and then pooled by meta-analysis. Correction was made for testing of multiple correlated phenotypes using a 5% false discovery rate threshold. Heterogeneity between MR estimates for different instruments was used to indicate possible bias due to effects of the genetic variants through pathways unrelated to iron status. There were 904 distinct phenotypes included in the MR-PheWAS analyses. After correcting for multiple testing, the three genetic instruments for systemic iron status demonstrated consistent evidence of a causal effect of higher iron status on decreasing risk of traits related to anemia (iron deficiency anemia: odds ratio [OR] scaled to a standard deviation increase in genetically dete